Potential protein post-translational modification in ERp57: A phenotype marker for male fertility - Viroj Wiwanitkit (Wolters Kluwer Medknow Publications, 2010)
Background : In protein expression, post-translational modification is an important process. It is also an important process in human reproductive science. ERp57 is a molecule that is mentioned for post-translational modification. ERp57 is a component of human sperm acrosome proteins. However, the data on post-translational modifications of ERp57 is limited. Aim: The aim of this work is to assess potential protein post-translational modifications in ERp57 protein. Settings and Design : A descriptive computational bioinformatics study. Materials and Methods : In this work, potential protein post-translational modifications in ERp57 protein were assessed via a standard bioinformatics technique. Statistical Analysis Used : Bioinformatics analysis. Results : There are three post-translational modifications within ERp57 from bioinformatics analysis. Conclusion : This new knowledge can be useful for better realization on molecular process of male infertility.